Excavatolide E triggers oxidative stress-associated apoptosis and DNA damage to inhibit bladder cancer cell proliferation - Che-Wei Yang; Chia-Hung Yen; Tsu-Ming Chien; Szu-Yin Yu; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (Molecular Biology Reports, 2026)

Electron-percolation-driven electric-field harmonization reprograms Zn nucleation for ultrastable Zn metal anodes - Jia-Sheng Lin; Daniel Chang; Che-Ning Yeh; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2026)

Agricultural management intensity drives niche partitioning of ammonia oxidizers at three contrasting soil sites - Yu Zeng; Che Tan; Chang Yin; Xiaozhong Wang; Hongsheng Gao; Hua Peng; Yongchao Liang (Applied Soil Ecology, 2026)

Conserved crop root economics space drives niche partitioning of ammonia oxidizers - Yu Zeng; Che Tan; Zhihui Wen; Jianbo Shen; Chang Yin; Yongchao Liang (Soil Biology and Biochemistry, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

The enhanced nitrous oxide emissions are driven by prokaryotic ammonia oxidizers and nirK-denitrifiers under various combinations of nitrogen and rice straw in a paddy soil - Chunyan Wu; Yinxiu Liu; Xu Tang; Tao Sun; Che Tan; Yu Zeng; Yan Li; Chang Yin; Yongchao Liang (Soil Ecology Letters, 2026)

The rupture process of the September 2022 Guanshan and Chishang Earthquakes: Joint inversion of seismological and geodetic data - Wei-Yu Zhang; Yu-Sheng Sun; Yopi Serhalawan; Po-Fei Chen; Ming-Che Hsieh; Wu-Lung Chang (Journal of Asian Earth Sciences, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Boosting catalytic activity toward industrial water electrolysis: Ag–triggered dual–site activation in NiFe LDH for ultra–efficient oxygen evolution reaction - Habib Gemechu Edao; Chia-Yu Chang; Woldesenbet Bafe Dilebo; Chemeda Barasa Guta; Keseven Lakshmanan; Endalkachew Asefa Moges; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Chun-Chi Chang; Wei-Sheng Liao; Meng-Che Tsai; Wei-Nien Su; et al. (Chemical Engineering Journal, 2026)

Long-term substitution of chemical fertilizer with organic manure enhances the activity and autotrophic growth of ammonia-oxidizing archaea and comammox nitrospira in paddy soil - Chunyan Wu; Xu Tang; Che Tan; Tao Sun; Yu Zeng; Yinxiu Liu; Yingxia Liu; Yan Li; Yongchao Liang; Chang Yin (Journal of Environmental Management, 2025)

Decisive electrocatalyst of oxyphilic transition metals with bivalent metal perovskites: Localized oxygen confinement for enhanced 2e-WOR in H₂O₂ production - Chemeda Barasa Guta; Chia-Yu Chang; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Endalkachew Asefa Moges; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2025)

Sodium silicate complex reduces subdermal hemorrhage and prolongs survival after envenomation by Trimeresurus stejnegeri stejnegeri - Yen-Chia Chen; Hao-Ming Chang; Chang-Chih Ke; Chia-Chun Liu; Yu-Kai Huang; Kun-Che Chang; Min-Hui Chen; Isaac Chun-Jen Chen; Yu-Wei Chiang; Po-Yu Liu; Chih-Sheng Lai; Kuo-Lung Lai; et al. (Toxicon, 2025)

Chemical structure and bioactivities of a sulfated polysaccharide from precious medicinal fungi - Mei-Kuang Lu; Chi-Hsein Chao; Tsu-Yuan Chang; Ming-Che Cheng; Yu-Chi Hsu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Feasibility and limitations of using specific nitrification inhibitors to differentiate ammonia oxidizer activity - Che Tan; Yu Zeng; Cécile Gubry-Rangin; Chang Yin; Yongchao Liang (Soil Biology and Biochemistry, 2025)

Field experiment study to assess critical wave conditions leading to failure of mangrove Rhizophora stylosa - Nobuhito Mori; Che-Wei Chang; Kenji Ono; Hironori Noguchi; Shigeyuki Baba; Hideaki Yanagisawa; Toyohiko Miyagi; Naoki Tsuruta; Kojiro Suzuki; Shiro Yamagata; Yusuke Hasegawa; Yu-Lin Tsai; et al. (Coastal Engineering, 2025)

Using unmanned aerial vehicle monitoring for the landslide and dammed lake: a case study of the Xiuluan area in Taiwan - Che-Hsin Liu; Jui-Yi Ho; Horn-Ru Liao; Shih-Chiang Lee; Naoki Sakai; Chen-Yu Chen; Chih-Hsin Chang (Bulletin of Engineering Geology and the Environment, 2025)

High content heteroatoms doped and valuable biomass derived activated carbon composited with graphene for high performance supercapacitors - Ming-Che Cheng; Yu-Sung Chang; Du-Cheng Tsai; Yen-Lin Huang; Fuh-Sheng Shieu (Fuel, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Comprehensive validation of a compact laser speckle contrast imaging system for vascular function assessment: from the laboratory to the clinic - Meng-Che Hsieh; Chia-Yu Chang; Ching-Han Hsu; Congo Tak Shing Ching; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Novel electrocatalyst with abundant oxygen vacancies enabling efficient two-electron water oxidation reaction for H2O2 synthesis - Chemeda Barasa Guta; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Chia-Yu Chang; Fikiru Temesgen Angerasa; Endalkachew Asefa Moges; Yosef Nikodimos; Keseven Lakshmanan; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Deciphering the functional importance of comammox vs. canonical ammonia oxidisers in nitrification and N2O emissions in acidic agricultural soils - Che Tan; Chang Yin; Lei Zhang; Yu Zeng; Cécile Gubry-Rangin; Hao Chen; Zixiang Gao; Hongyun Peng; Tingqiang Li; Yongchao Liang (Soil Biology and Biochemistry, 2024)

Traction-based implementation of transmitting boundaries for nonlinear seismic Soil–Structure interaction analyses - Che-Yu Chang; Wen-Chia Yang; Chen-Hsiang Kuo (Soil Dynamics and Earthquake Engineering, 2024)

Exposure to phenols reduces melanogenesis in B16F10 cells and zebrafish - Chung-Yu Lin; Chang-Yi Wu; Chia C. Wang; Che-Hsin Lee (Aquatic Toxicology, 2024)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Designing, analyzing, and experimentally verifying a uniaxial shear box for investigating the length effect of buried pipelines during soil liquefaction - Hsuan-Chih Yang; Che-Yu Chang; Kuan-Yu Chen; Hsin-Chen Chou (Transportation Geotechnics, 2023)

Analysis and classification of coffee beans using single coffee bean mass spectrometry with machine learning strategy - Jia-Jen Tsai; Che-Chia Chang; De-Yi Huang; Te-Sheng Lin; Yu-Chie Chen (Food Chemistry, 2023)

Ultrafine particles in urban settings: A combined study of volatility and effective density revealed by VT-DMA-APM - Che-An Wu; Yu-Ting Chen; Li-Hao Young; Po-Kai Chang; Li-Ti Chou; Albert Y. Chen; Ta-Chih Hsiao (Atmospheric Environment, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Field experiments: How well can seismic monitoring assess rock mass falling? - Jui-Ming Chang; Wei-An Chao; Yu-Ting Kuo; Che-Ming Yang; Hongey Chen; Yu Wang (Engineering Geology, 2023)

High-entropy transition metal disulfide colloid clusters: synergistic atomic scale interaction and interconnected network for ultra-stable potassium ion storage - Yan-Jie Liao; Wei-Wen Shen; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Effect of support condition on the mechanical behavior of ductile iron pipes buried at shallow depth within the backfill of controlled low strength material - Hsuan-Chih Yang; Che-Yu Chang; Gee-Yu Liu; Pao-Ching Chou (Transportation Geotechnics, 2023)

Production and analysis of metabolites from solid-state fermentation of Chenopodium formosanum (Djulis) sprouts in a bioreactor - Chen-Che Hsieh; Shu-Han Yu; Kai-Wen Cheng; Yu-Wei Liou; Cheng-Chih Hsu; Chang-Wei Hsieh; Chia-Hung Kuo; Kuan-Chen Cheng (Food Research International, 2023)

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Responsiveness to contest experiences is associated with competitive ability but not aggressiveness or boldness - Yu-Ju Chen; Yu-Ting Chang; Yung-Che Tseng; Yuying Hsu (Behavioral Ecology and Sociobiology, 2022)

On-Site Investigations of Coastal Erosion and Accretion for the Northeast of Taiwan - Ting-Yu Liang; Chih-Hsin Chang; Shih-Chun Hsiao; Wei-Po Huang; Tzu-Yin Chang; Wen-Dar Guo; Che-Hsin Liu; Jui-Yi Ho; Wei-Bo Chen (Journal of Marine Science and Engineering, 2022)
Coastal erosion is a major natural hazard along the northeastern shoreline (i.e., Yilan County) of Taiwan. Analyses of the evolution of the 0 m isobath of the Yilan County coastline indicate that erosion and accretion are occurring north and south of Wushi Fishery Port, respectively, because of jetty and groin construction. Topographic and bathymetric surveys involving the measurement of 43 cross sections were conducted in 2006, 2012, 2013, and 2019. The cross-shore profile comparisons reveal that the erosion of onshore dunes is significant in the northern Jhuan River estuary. Due to the establishment of a nature reserve in the southern Lanyang River estuary, the sediments are carried northward by tidal currents, and accretion is inevitable in the northern Lanyang River estuary. The results of the bathymetric surveys also suggest that the shoreline of Yilan County tends to accrete in summer because of abundant sediment from the rivers; however, it is eroded in winter, owing to the large waves induced by the northeast monsoon. Additionally, the calculated net volume of erosion and accretion between each pair of cross sections shows that the length of coastline impacted by estuarine sediment transport is approximately 2 km long from north to south along the coastline of the Lanyang River estuary.

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

Studies on the Development of Small Abalone ( Haliotis diversicolor supertexta ) Essence and its Antioxidative Properties - Yu-Wei Chang; Chun-Che Lin; Wen-Chieh Sung (Journal of Aquatic Food Product Technology, 2018)

Assessing typhoon damages to Taiwan in the recent decade: return period analysis and loss prediction - Chia-Jeng Chen; Tsung-Yu Lee; Che-Min Chang; Jun-Yi Lee (Natural Hazards, 2018)

Neonatal Dexamethasone Treatment Exacerbates Hypoxia/Ischemia-Induced White Matter Injury - Chia -Yu Yeh; Che-Ming Yeh; Ting-Hsuan Yu; Kan-Hsun Chang; Chiung-Chun Huang; Kuei-Sen Hsu (Molecular Neurobiology, 2017)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Elucidation of anti-Vibrio factors associated with green alga Picochlorum sp. strain S1b - Jung-Che Kuo; Yu-Han Chang; Tsung-Yuan Chen; Yi-Min Chen (Journal of Applied Phycology, 2015)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Reversine, a 2,6-disubstituted Purine, as an Anti-cancer Agent in Differentiated and Undifferentiated Thyroid Cancer Cells - Shih-Che Hua; Tien-Chun Chang; Hau-Ren Chen; Chieh-Hsiang Lu; Yi-Wen Liu; Shu-Hsin Chen; Hui-I Yu; Yi-Ping Chang; Ying-Ray Lee (Pharmaceutical Research, 2012)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)